2019
DOI: 10.1007/978-3-030-35802-0_30
|View full text |Cite
|
Sign up to set email alerts
|

4-Connected Triangulations on Few Lines

Abstract: We show that 4-connected plane triangulations can be redrawn such that edges are represented by straight segments and the vertices are covered by a set of at most p 2n lines each of them horizontal or vertical. The same holds for all subgraphs of such triangulations.The proof is based on a corresponding result for diagrams of planar lattices which makes use of orthogonal chain and antichain families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Xin He [34] used transversal structures to give an algorithm for realizing these triangulations as the contact graphs of rectangles (equivalently, drawing their dual in such a way that every face is a rectangle), and together with Goos Kant showed that the transversal structure and drawing can be computed in linear time [35]. Since then, several other graph drawing algorithms based on transversal structures have been obtained [9,18,22,23,30].…”
Section: Introductionmentioning
confidence: 99%
“…Xin He [34] used transversal structures to give an algorithm for realizing these triangulations as the contact graphs of rectangles (equivalently, drawing their dual in such a way that every face is a rectangle), and together with Goos Kant showed that the transversal structure and drawing can be computed in linear time [35]. Since then, several other graph drawing algorithms based on transversal structures have been obtained [9,18,22,23,30].…”
Section: Introductionmentioning
confidence: 99%
“…Answering a question of Chaplick et al [3] he also constructed a family of subcubic series-parallel graphs with unbounded π 1 2 -value. Felsner [11] proved that, for every 4-connected plane triangulation G on n vertices, it holds that π 1 2 (G) ≤ √ 2n. Chaplick et al [4] also investigated the complexity of computing the affine cover numbers.…”
Section: Introductionmentioning
confidence: 99%